Survival outcomes of sex cord-stromal tumors of the ovary - Krittiya Somaketarin (2020)
©2020 Somaketarin et al. Objective: To evaluate the role of retroperitoneal lymphadenectomy and the survival outcomes of malignant ovarian sex cord-stromal tumors (SCSTs). Materials and Methods: Patients with malignant SCSTs of the ovary who underwent surgery between January 2005 and March 2017 were retrospectively reviewed. The authors analyzed stage, histology, clinical presentation, type of surgery, the role of lymphadenectomy, five-year disease-free survival, and five-year overall survival. Results: Fifty-four patients with malignant SCSTs of the ovary were identified in this study. Retroperitoneal lymph node dissection was performed in 30 (55.6%) patients. No lymph node metastasis was detected. At the median follow-up time of 35 months, the five-year disease-free survival and the five-year overall survival was 88.7% and 92.4%, respectively. Conclusion: The survival outcomes of women with ovarian sex cord-stromal malignancies are favorable. No lymph node metastasis is detected in this study. Retroperitoneal lymphadenectomy may be omitted in a surgical staging procedure for these patients.